Evaluation of financial and analytical activities of the biggest car makers of the Russian federation - Akhmadeev, Ravil Gabdullaevich; Bykanova, Olga Alekseevna; Morozova, Tatiana Victorovna; Safonova, Emiliya Gennadyevna; Turishcheva, Tatiana Borisovna; Lehoux, Liubov (Penerbit Universiti Kebangsaan Malaysia, 2018)
Companies need an internal management control system to develop successfully in the current conditions of a market economy. This statement is true irrespective of an organisational form of a company. Financial indicators (such as profit) can give a full picture of absolute effectiveness of the company's performance. The main activities of any company can be split into the following groups: production, sales, procurement, financial and investment activities. According to the 2013-2016 consolidated financial statements prepared under IFRS, Russia’s largest car producers include AVTOVAZ Group, GAZ Group, KAMAZ Group and SOLLERS Group. They all used a three-factor model of return on equity and other mathematical tools. Analysis of the three-factor model of return on equity enabled us to formulate several statements. The main factor affecting return on equity is the sales margin. When the sales margin is measured within a certain period of time, there can be either a negative or a positive influence on the final financial results of a company. The two other factors that influence return on equity are less significant. The factor of margin is the most significant and the index of capital intensity is the least significant factor of the three. Our practical innovation is a new model to analyse financial reporting of a car making company, which showcases the financial position of a company.